THE USE OF VIDEOS AS A MEDIUM OF INSTRUCTION FOR EFL IRAQI COLLEGE STUDENTS' PERFORMANCE IN GRAMMAR - Khansa Hassan Al-Bahadli (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study is an attempt to find out the effect of the online video texts on EFL college students’ performance in Grammar subject. To achieve the aim of the study, the following hypothesis has been tested. There is no significant difference between the experimental group performance and that of the control group in the score of the post test. Sixty students from the College of Al-imam Al-kadhum have been randomly chosen (thirty students as an experimental group which are taught grammar by the use of online videotext and thirty students as a control group which are taught grammar according to the conventional ways), during the academic year 2019 -2020. The researcher herself has taught both groups the assigned material (eight selective topics). Statistical analysis of data achieved through the test indicates that there are statistically significant differences between the experimental group performance and that of the control group in favors of the experimental group. In the light of these results, some recommendations are presented.